DESCRIPTION OF TOTAL CHOLESTEROL LEVELS IN ACTIVE SMOKERS USING THE CHOLESTEROL OXIDASE PEROXSIDASE AMINOANTYPIRIN (CHOD-PAP) METHOD IN PUSKESMAS KABILA - cindi Afriyani cindi; Arpin; Rusdin (LPPM Universitas Bina Mandiri Gorontalo, 2021)
Smoking can cause various health problems such as disorders of the blood vessels, deaths caused by vascular system diseases in Indonesia totaling 468,700 people or it is the 6th largest of all WHO group countries. This is because cigarette smoke contained in tobacco is one of the substances that can interfere with the body's work and affect cholesterol metabolism in the body, damaging the walls of blood vessels so that it makes it easier for fats to stick to the walls of the blood vessels. The purpose of this study was to describe the total cholesterol levels in active smokers using the Cholesterol Oxidase Peroxsidase Aminoantypirin (CHOD-PAP) method. This research is a quantitative descriptive study using simple random sampling technique. The population in this study were 428 active smokers with a sample of 28. Sampling was carried out at the district health center, bone bolango district, and an examination was carried out at the Regional Health Laboratory Center of Gorontalo Province from 12 to 16 October using a 5010 photometer. Based on the research results found 18 respondents who who have high total cholesterol levels with a percentage of 64.3% and 10 respondents who have normal total cholesterol levels with a percentage of 35.7% and factors that can affect total cholesterol levels in smokers are genetics, age and habits of consuming high-fat foods. Active smokers are advised to stop consuming cigarettes or reduce the number of cigarettes consumed.